Pengaruh Growth Mindset terhadap Hasil Belajar Materi Teorema Pythagoras melalui Mediasi Self-Efficacy - Sabriyani, Syifa; Prayitno, Sudi; Kurniawan, Eka (FKIP Universitas Mataram, 2025)
This study aims to examine the effect of growth mindset on self-efficacy, as well as its influence on students’ learning outcomes in the Pythagoras' Theorem topic, both directly and indirectly through the mediation of self-efficacy, among eighth-grade students at SMPN 15 Mataram in the 2024/2025 academic year. This research employed a quantitative approach with an ex-post facto design. The population consisted of 371 students, and a sample of 54 students from classes VIII-B and VIII-G was selected using cluster random sampling. Data were collected through questionnaires and tests, and analyzed using SPSS software along with the Macro PROCESS Model 4 to test the mediation model. The results showed that 1) growth mindset had a positive and significant effect on students’ self-efficacy (a=0,740, p<0,001); 2) there was no significant direct effect of growth mindset on learning outcomes (c'=0,349, p=0,249); 3) there was a positive and significant indirect effect of growth mindset on learning outcomes through the mediation of self-efficacy (ab=0,930, CI [0,478 to 1,438]), indicating full mediation. Thus, self-efficacy is proven to act as a full mediator in the relationship between growth mindset and students’ learning outcomes.